(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A survey was conducted to get an overview and to gather information on the existing and socioeconomic condition of the SIDR affected people and migration. To perform this study data were collected from the three selected village (south Shailkati, Hothkhali and Lahori) affected people by random sampling after selecting the study topic and area. Then the data were processed and analyzed through using different statistical tools like pie-chart, bar diagram, table etc. The GoB and NGOs subsidiaries, also help the SIDR victims to cope with the situation. From the study we found that the NGOs contributed more to adapt with the situation. After SIDR the occupation of non-agriculture day-labour increased (37%) and the occupation of agriculture decreased 31% from 55.64%. After SIDR middle income group people were greatly affected. The income and expenditure of middle income group people were found to reduce. Low income group people increased their income and expenditure was decreased. After SIDR due to decrease their average income, they could not manage their basic needs. The food habit of the affected people was also changed. They took more flour rather than rice. The scarcity of agricultural production created the reduction of food stock. Most of the respondents had no food stock. The rate of internal migration was also increased. The rate of migration to other places (47%) and Dhaka (53%) was increased due to SIDR. But the situation was better than close post SIDR period. Most of the cases they are adopting with the changing socio-economic conditions. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22094 J. Environ. Sci. & Natural Resources, 6(2): 43-47 2013